The LEAD trial—The effectiveness of a decision aid on decision making among citizens with lower educational attainment who have not participated in FIT-based colorectal cancer screening in Denmark: A randomised controlled trial. Issue 2 (February 2020) - Gabel, Pernille; Edwards, Adrian; Kirkegaard, Pia; Larsen, Mette Bach; Andersen, Berit
Highlights: Decision aids may increase screening uptake among citizens with lower educational attainment. The web-based decision aid did not show an overall effect on informed choice. A population shift towards more positive attitudes and less decisional conflict may be induced. Abstract: Objectives: This trial tested the effectiveness of a self-administered web-based decision aid, targeted at citizens with lower educational attainment, on informed choice about colorectal cancer screening participation as assessed by group levels of knowledge, attitudes and uptake. Methods: The randomised controlled trial was conducted among 2702 screening-naïve Danish citizens, 53–74 years old, with lower educational attainment. Baseline questionnaire respondents (62%) were allocated to intervention and control groups. Intervention group citizens received the decision aid. Outcomes were informed choice, worries and decisional conflict. Results: Analyses were conducted among 339 eligible citizens. The mean difference in knowledge score change between intervention and control group was 0.00 (95% confidence interval (CI): -0.38;0.38). Trends towards more positive screening attitudes (mean difference in score change: 0.72, 95% CI: -0.38;1.81) and higher screening uptake (7.6%, 95% CI:−2.2;17.4%) were observed. Worries (−0.33, 95% CI: −0.97;0.32) and decisional conflict (mean difference: −3.5, 95%CI: −7.0;−0.1) were slightly reduced. Conclusions: The decision aid did not affect informed choice or knowledge. However, there were trends towards increased screening uptake and more positive screening attitudes. Practice implications: Being a simple intervention and easily administered, the decision aid could represent a cost-effective way of enhancing screening uptake, and some elements of informed decision-making.